(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The aim of the research is to assess the practice of tax administration to diminish the strategic direction of (proactive, analytical, defensive, response) and the nature of its relationship to organizational excellence represented by (leadership, strategic planning, focus on taxpayers, information and analysis and knowledge management, focus on operations, focus on forces. The questionnaire was adopted as a main tool in collecting data and information from the sample members of the General Authority for Taxes (110) who are in the site (m. Second Division Manager, Ms The statistical program (SPSS) was used to calculate (mean, standard deviation, difference coefficient, correlation coefficient, t-test). The research reached a number of conclusions, the most prominent of which were: 1- The level of response of tax administration leaders towards the practice of strategic direction is high. 2. There is a positive and strong correlation between the dimensions of strategic direction and organizational excellence.